2002
DOI: 10.1016/s0168-6496(02)00392-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of bacterial diversity in Lodgepole pine (Pinus contorta) rhizosphere soils from British Columbia forest soils differing in disturbance and geographic source

Abstract: Rhizosphere bacteria from Lodgepole pine (Pinus contorta) seedlings were characterized from forest soils which differed in disturbance and geographic source. Soil disturbance treatments included whole-tree harvesting with and without heavy soil compaction and whole-tree harvesting with complete surface organic matter removal and heavy soil compaction from British Columbia (BC) Ministry of Forests Long-Term Soil Productivity installations in three biogeoclimatic subzones in central BC, Canada. Bacterial communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 28 publications
4
48
0
1
Order By: Relevance
“…Acidobacteria and Proteobacteria are generally the most numerically dominant phyla in soil, while members of Bacteroidetes and Firmicutes are less common (Dunbar et al 1999;Chow et al 2002;Fierer et al 2005). In this study, we also found Proteobacteria and Acidobacteria to be dominant.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Acidobacteria and Proteobacteria are generally the most numerically dominant phyla in soil, while members of Bacteroidetes and Firmicutes are less common (Dunbar et al 1999;Chow et al 2002;Fierer et al 2005). In this study, we also found Proteobacteria and Acidobacteria to be dominant.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, we also found Proteobacteria and Acidobacteria to be dominant. Members of aProteobacteria were the most abundant bacteria in 16S rDNA clone libraries derived from Long-Term Soil Productivity (LTSP) forest soil from British Columbia, Canada (Chow et al 2002), Australian forest soils (Stackebrandt et al 1993), Scotland grassland rhizosphere soil (McCaig et al 1999), and fertilizer-applied soil (Toyota and Kuninaga 2006). Members of Acidobacteria were the most abundant in the clone libraries from Arizona pinyon pine rhizosphere and bulk soils (Dunbar et al 1999), and in desert, prairie, and forest soils (Fierer et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Culture-independent analyses performed with various plants often reveal that members of the (former) Cytophaga-Flavobacterium-Bacteroidetes constitute a dominant fraction of the rhizobacteria, as with Lolium perenne (Marilley and Aragno 1999), maize (Zea mays; Chelius and Triplett 2001) or Lodgepole pine (Pinus contorta; Chow et al 2002), and cucumber (Cucumis sativus; Green et al 2006). In this latter publication, in which the rhizobacteria associated with the transition from seeds to root were analyzed, Chryseobacterium (Bacteroidetes) and Oxalobacteraceae (ß proteobacteria) were the most persistent populations.…”
Section: Bacteriamentioning
confidence: 99%
“…However, while Kaiser et al (2001) also found dominant Bacteroidetes populations in canola (Brassica napus), Smalla et al (2001) did not, although both studies appear to have been conducted at the same location. Other groups that may dominate the rhizosphere as shown by cultureindependent analyses, include Acidobacterium, Verrucomicrobia, Gemmatimonadetes and Nitrospirae (Ludwig et al 1997;Singh et al 2007;Filion et al 2004;Chow et al 2002).…”
Section: Bacteriamentioning
confidence: 99%
See 1 more Smart Citation